Changes in composition and structure of a tropical dry forest following intermittent Cattle grazing - Margaret Stern; Mauricio Quesada; Kathryn E. Stoner (Revista de Biología Tropical, 2002)
In northwestern Costa Rica, cattle are being used as a "management tool" to reduce the amount of combustible material, mainly dominated by Hyparrhenia rufa, an African grass. This project is being developed within Parque Nacional Palo Verde and Reserva Biológica Lomas Barbudal, both of which fonn part of the only remaining tropical dry forests in Mesoamerica. To determine the short-term effects of cattle grazing on the natural vegetation, we compared the floristic composition within Palo Verde in an area under intermittent cattle grazing with an area that has not been grazed. There were significantly fewer plant species in the area with intermittent cattle grazing compared to the area with no grazing. Floristic composition of these two habitats was different as reflected by both Fisher's alpha values and the Shannon index of diversity, both of which were significantly higher in the ungrazed site. The ungrazed area contained more plant species and was more similar to mature forest. The structure of the vegetation was significantly different between the intermittently grazed and ungrazed sites with more small stems (1-5 cm dbh) and fewer large stems (>5 cm dbh) in the intermittently grazed habitat. These results indicate that cattle grazing has an impact on the dry forest by reducing the relative abundance and density of larger tree species and by changing the species composition and structure of the community. The current management plan implemented in Palo Verde and Lomas Barbudal is not appropriate because of the impact that cattle have on the structure of the natural vegetation and should not be considered a viable alternative in other protected areas of dry forest in the Neotropics. We suggest that alternative fire prevention measures be evaluated including hand-cutting H. rufa, the creation of more frequent and larger fire breaks, and the development of green breaks. En el noroeste de Costa Rica se utiliza ganado como una "herramienta de manejo" para reducir la cantidad de material combustible, principalmente Hyparrhenia rufa, un zacate que proviene de Africa. Este proyecto se desarrolla dentro del Parque Nacional Palo Verde y la Reserva Biológica Lomas Barbudal, ambos forman parte de los últimos remanentes de bosque tropical seco de Mesoamérica. Con el fin de determinar los efectos a corto plazo del pastoreo de ganado vacuno sobre la vegetación natural, realizamos un muestreo dentro de Palo Verde para comparar la composición florística de un área de pastoreo intermitente con un área sin pastoreo. Encontramos significativamente menos especies de plantas en el área con pastoreo intermitente comparado con el área sin pastoreo. La composición florística de estos dos hábitats fue significativamente diferente basada en una comparación del alfa de Fisher y el índice de Shannon de diversidad; ambos fueron significativamente más altos en el área sin pastoreo. El área no pastoreado tuvo mayor número de especies y mayor semejanza con bosque maduro. La estructura de la vegetación fue significativamente diferente entre las dos áreas pastoreadas y no pastoreadas, con mayor número de individuos de diámetros pequeños (1-2.5 cm) y menor número de individuos de diámetros grandes (>5 cm) en el área con pastoreo intermitente. Estos resultados sugieren que el ganado reduce la abundancia relativa y la densidad de las especies de árboles y cambia la composición florística y estructura del bosque tropical seco. El plan de manejo actual de Palo Verde y Lomas Barbudal no es apropriado debido al impacto que el ganado tiene sobre la estructura de la vegetación natural y no debe ser considerado como una alternativa viable para otras áreas protegidas del neotropico. Sugirimos que se evalúen métodos alternativos para prevenir incendios, como el corte de jaragua (Hyparrhenia rufa) con machetes, la creación de rompefuegos en mayor cantidad y magnitud, y rompefuegos verdes.